1995
DOI: 10.1017/s0266466600009713
|View full text |Cite
|
Sign up to set email alerts
|

Spurious Break

Abstract: A quasi-maximum likelihood estimator of the break date is analyzed. Consistency of the estimator is demonstrated under very general conditions, provided that the data-generating process is not integrated. However, the asymptotic distribution of the estimator is quite different for time series that are integrated of order one. In that case, when there is no break, the analyst can be spuriously led to the estimation of a break near the middle of the time series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…In both cases, the fitted regression coefficients turn out to be statistically significant with probability one asymptotically and this is true even when robust standard errors that account for residual autocorrelation are used to assess significance [17]. Some related results have been shown to hold for trend breaks, fractional processes and regressions among such variables (e.g., [1,[11][12][13][14]28]) even when they are stochastically independent, the latter being the phenomenon originally examined in simulations by Granger and Newbold [6].…”
Section: No One Understands Trendsmentioning
confidence: 86%
See 1 more Smart Citation
“…In both cases, the fitted regression coefficients turn out to be statistically significant with probability one asymptotically and this is true even when robust standard errors that account for residual autocorrelation are used to assess significance [17]. Some related results have been shown to hold for trend breaks, fractional processes and regressions among such variables (e.g., [1,[11][12][13][14]28]) even when they are stochastically independent, the latter being the phenomenon originally examined in simulations by Granger and Newbold [6].…”
Section: No One Understands Trendsmentioning
confidence: 86%
“…More generally, for every value of K we get from (15) a class of predictors corresponding to the leading K trend components in the process. Let N = [np], and N + h = [nr] so that (14) and (15) effectively provide h-step ahead optimal predictors of these components. E{η k (r)|F p } may be estimated from sample data bŷ…”
Section: Trend Coordinates and Predictionmentioning
confidence: 99%
“…The Zivot-Andrews test does not assume a structural break under the null and the alternative hypotheses but the Perron test allows for a break under the null and alternative hypotheses. Nunes et al (1997) suggested that there may be some size distortion for Zivot-Andrews test. The first step of the Kim-Perron procedure is a pre-test for the break date.…”
Section: Results (Note 10)mentioning
confidence: 99%
“…Bhattacharya et al (1983) , Künsh (1986), Perron (1989, Teverosky and Taqqu (1997), Giraitis et al (2001), Mikosch and Starica (2004) , Perron and Qu (2004) and many others). Other authors have studied the opposite effect, that is, how conventional procedures for detecting and dating structural changes tend to find spurious breaks, usually in the middle of the sample, when in fact there is only fractional integration (see Nunes et al (1995), Krämer and Sibbertsen (2002) and Hsu (2001)). …”
Section: The Test Work As Followsmentioning
confidence: 99%